Predictors of blood loss in lung transplant surgery—a single center retrospective cohort analysis - Grande, Bastian; Oechslin, Pascal; Schlaepfer, Martin; Seifert, Burkhardt; Inci, Ilhan; Opitz, Isabelle; Spahn, Donat R.; Weder, Walter; Zalunardo, Marco (Journal of Thoracic Disease, 2019)
Background: This retrospective study aims to identify clinical predictors of intraoperative blood loss during lung transplantation. While for other surgical specialties predictors of blood loss have been identified such as previous likewise located surgery, poor preoperative health status of patients, blood coagulation status, and use of extra corporeal circulation, predictors of blood loss during lung transplantation are not yet established. Methods: A total of 326 lung transplants were performed between January 2000 and February 2014 at a tertiary hospital. The primary aim was to associate blood loss with the following potential predictors: pulmonary arterial hypertension, pre- or intraoperative extracorporeal life support (ECLS), previous thoracic surgery, previous lung transplant, and Charlson Comorbidity Index (CCI). Postoperative complications and 30-day mortality were secondary endpoints of the study. Results: Median estimated blood loss during lung transplant was 1,500 mL (IQR, 1,000–2,875 mL). Pre- and intraoperative ECLS (P=0.02, P